Effect of stiffness of protected secondary edge beams on the membrane behaviour of composite beam-slab systems in fire - Nguyen, Tuan-Trung (2016)
This paper presents the experimental behaviour on two one-quarter scale composite beam-slab systems in fire. The aim was to study the effect of bending stiffness of protected secondary edge beams on the fire behaviour of floor assemblies. Two specimens were denoted as P215-M1099 and P486-M1099. To investigate the effect of second moment of area about the major axis of the protected secondary beam (IyPSB), IyPSB of P486-M1099 was increased 2.26 times compared to that of P215-M1099. The main and unprotected secondary beams of two specimens were kept the same. The test results showed that as the stiffness of the protected secondary edge beam increased, the slab deflection decreased and failure of the slab occurred later. However, composite action between the edge beams and the concrete slab played a key role in mobilising this beneficial effect. Once the composite action had been weakened by parallel cracks in the slab over the main or secondary edge beams, the slab would lose the benefit associated with the greater stiffness of the protected secondary edge beams.